Treatment decision‐making among men with lower urinary tract symptoms: A qualitative study of men's experiences with recommendations for patient‐centred practice. Issue 1 (14th October 2020) - Selman, Lucy E.; Clement, Clare; Ochieng, Cynthia A.; Lewis, Amanda L.; Chapple, Christopher; Abrams, Paul; Drake, Marcus J.; Horwood, Jeremy
Abstract: Aims: To inform and guide patient‐centred care for men with lower urinary tract symptoms (LUTS), by providing in‐depth qualitative evidence regarding men's perspectives on treatment decision‐making for LUTS. Methods: An interview study of men recruited from 26 English urology departments. Purposive sampling captured surgical/nonsurgical treatment decisions, and diversity in demographics and symptom burden, in men who had urodynamics and those who did not. After diagnostic assessments, men were interviewed either pre‐treatment or after LUTS surgery. Thematic analysis was conducted. Participants' descriptions of how LUTS treatment decisions were made were categorised as patient‐led, doctor‐led, or shared. Results: A total of 41 men participated (25 pre‐treatment, 16 post‐surgery), ages 52–89. Twenty out of 41 described the treatment decision as shared with their consultant, 14 as doctor‐led, and seven as patient‐led. There was no obvious association between treatment decision‐making style and patients' satisfaction with either clinicians' role in their decision or their treatment decision. Incomplete or rushed discussions and misperceptions of LUTS and its treatment were reported, indicating a risk of suboptimal decision‐making support by clinicians. As well as clinician opinion, men's treatment decision‐making was influenced by the results of urological assessments, comparing current symptoms with possible side‐effects of surgery, and others' experiences and opinions. Conclusions: Men with LUTS report and prefer different kinds of decision‐making support from their clinicians, who must tailor their input to patients' preferences and needs. Patients' treatment decision‐making involves multiple factors and can be challenging, and areas of inadequate clinician support were identified. Recommendations for patient‐centred consultations about LUTS treatment are presented.